Technical Assessment and Optimization of Off-Gas Cooling in Nickel Matte Pyrometallurgy Based on Carbon Variation - Sabrianah Badaruddin; Alif Nur Laili Rachmah; Muhammad Ikhsan Taipabu; Farida Diyah Hapsari; Esther Muatiara Santallum Ekklesia Tibalia (Candela Edutech Indonesia, 2026)
Exhaust gas emission management is a critical aspect of pyrometallurgical nickel smelting because it directly affects energy efficiency, operational safety, and overall process sustainability. This study investigates the influence of calcine carbon content on exhaust gas formation and determines the required cooling air volume in an industrial electric furnace operating at approximately 150 tons per hour. The research is based on deterministic mass and energy balance modelling developed from actual operational data obtained from a nickel smelting facility. The analysis quantifies the relationship between carbon oxidation reactions and off-gas generation during the smelting process. Results reveal a strong linear correlation between increasing calcine carbon content and exhaust gas volume. At an average carbon content of 1.96 %, the furnace produces 47,241 Nm³/h of exhaust gas. Under these operating conditions, a cooling air injection of 9,292 Nm³/h is required to reduce the gas temperature from 1000 °C to 800 °C in order to maintain safe furnace operation. The findings demonstrate that precise control of calcine carbon content and optimised cooling air design are essential for improving operational safety and efficiency in nickel smelting. The developed model provides a quantitative basis for designing safer and more efficient industrial off-gas control systems.